A MEMS Based Electrochemical Seismometer with Low Cost and Wide Working Bandwidth. (2016) - Sun, Zhenyuan; Chen, Deyong; Chen, Jian; Deng, Tao; Li, Guanglei; Xu, Chao; Wang, Junbo
Abstract: This paper reports a MEMS based electrochemical seismometer featured with low cost and wide working bandwidth. In this study, a new sensing unit was proposed, in which a pair of ultra-thin electrodes with large reactive surface areas were integrated on corresponding silicon substrates, leading to 1) an decrease in cost and an increase in yield due to the simplified fabrication processes (e.g., only three standard microfabrication steps); and 2) an increase in the working bandwidth (0.14Hz -26.81Hz) based on the optimized geometrical parameters, compared to conventional electrochemical seismometers (0.47Hz -18.24Hz).